PENGARUH KEAMANAN ASET PEMERINTAH DAERAH TERHADAP PENYALAHGUNAAN PERALATAN KANTOR: STUDI KASUS DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA SALATIGA - Seplina Wulandari; Marwata Marwata (Universitas Medan Area, 2020)
This research aims to describe the forms, preventions, intention of abuse, and intentions of report in abusing the official tool assets. In government, it is essential to have adequate asset management because a regional asset is the important resource for a regional government. The research is descriptively using with quantitative approach and primary data. The Sample used is non-probability sampling; purposive sampling. Data collection technique is survey. The research result pointed out that employee at Salatiga Public Work and Space Management Office assumed the use of office tools for personal use in working hours and outer of it, bringing them home, returning, and keeping them in the following time were forms of abusing office tools.